LIGHT RAYS IN THE EPOCH OF DARK MATTER DOMINATION - Chechin L.M; Kurmanov E.B; Konysbayev T.K (Academic Scientific Journal of Computer Science, 2019)
The cosmological Friedmann model has been generalized for the epoch of dark matter domination. In doing this its equation of state was chosen in the new - non-stationary form. The process of light propagation in such metric was explored and its refractive index was found.